Geriatrics and Aging through Transitional Environments (GATE) MS1 Curriculum: Obtaining a Functional History in the Home - Seema Limaye; Shellie Williams; Sandra Smith; Aliza Baron; Angela Blood (Association of American Medical Colleges, 2012)
Abstract Introduction This resource teaches medical students about geriatrics across the spectrum of care settings. Key components of this resource curriculum include a home visit, functional history-taking, and reflective writing. These were included because geriatric medical education literature has described in detail the benefits of home visits for medical students, including improving attitudes towards caring for the elderly and developing well-rounded physicians. Methods The 1.5-hour didactic session covers geriatric history-taking skills in addition to the components of a geriatric functional history, including administering screening tests for dementia, depression, and polypharmacy; vision and hearing deficits; and risk for impairments in activities of daily living and instrumental activities of daily living. During the last 30 minutes of the lecture, an independent, active, older adult answers questions about her social and health history. Following the lecture, pairs of students visit an assigned "trained patient" living in an independent senior building that is part of a retirement community. The students conduct a geriatric functional history and home safety assessment. Students' clinical interviewing skills are assessed by the trained patients, who deliver verbal feedback to the students and complete a structured written assessment. Students write a 250-word reflective essay about the encounter and complete brief, three-item knowledge questionnaires. Results Eighty-nine students completed a geriatric functional history-taking interview. All essays were evaluated using a grounded-theory qualitative analysis. The following themes were identified: surprise with patient independence, fascination with patient's life story, importance of home visit experience as part of the medical student training, student discomfort with certain interview content, learning from patients, and changing perceptions on aging. The trained patients rated students' skills as excellent overall. Open-ended comments were positive; some were congruent with themes derived from student essays. Discussion Despite successful implementation and medical school commitment to continuation of this curriculum, we identified several limitations of the curriculum. The administrative time required to schedule visits and training sessions could be resource intense and prohibitive for some medical schools. Also, we recognized significant variability in the quality and quantity of trained patient feedback.